2007
DOI: 10.1111/j.1365-2028.2007.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐tolerance mechanisms of common woody plant species in a semiarid savanna in south‐western Zimbabwe

Abstract: The frequency of fire has increased in savannas yet few studies have assessed how plants persist when subjected to long‐term disturbance by fire. We investigated the contributions of bark thickness and resprouting to the persistence of woody plants in two fire trials that were started in 1948 and 1949. The number of resprouts per individual, bark thickness, basal diameter and height of woody plants were measured in unburnt plots and those burnt annually, triennially and quinquennially during the late dry seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 15 publications
7
44
0
1
Order By: Relevance
“…In addition to recognising the importance of bark thickness to savanna tree dynamics under regimes of frequent fires ), there is a growing body of evidence that suggests that fire damage to the stem rather than the canopy crown is what kills trees (Gignoux et al 1997, Pinard and Huffman 1997, Balfour and Midgley 2006, Nefabas and Gambiza 2007, Midgley et al 2010). Balfour and Midgley (2006) demonstrated that among small stems in African savannas, the effects of fire on the xylem causes topkill.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to recognising the importance of bark thickness to savanna tree dynamics under regimes of frequent fires ), there is a growing body of evidence that suggests that fire damage to the stem rather than the canopy crown is what kills trees (Gignoux et al 1997, Pinard and Huffman 1997, Balfour and Midgley 2006, Nefabas and Gambiza 2007, Midgley et al 2010). Balfour and Midgley (2006) demonstrated that among small stems in African savannas, the effects of fire on the xylem causes topkill.…”
Section: Discussionmentioning
confidence: 99%
“…Although bark thickness is implicated in fire resilience, it has received much less attention as an explanation for the general fire resilience of savanna trees than either the escape diameter or escape height hypotheses (cf. Gignoux et al 1997, Pinard and Huffman 1997, Nefabas and Gambiza 2007, but see Hoffmann et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, stem survival after fire is arguably a function of fire intensity, the height, width and growth rate of the stem, and the bud-protective (bark) mechanisms on the stem (Gill and Ashton 1968;Gill 1995;Gignoux et al 1997). Of the plant traits that confer individual fire resistance, bark thickness is the most important so that only trees with thick bark, regardless of their stem height or width, usually survive very severe fires (Vines 1968;Hengst and Dawson 1994;Pinard and Huffman 1997;Nefabas and Gambiza 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fire plays an important role in savanna dynamics. Every landscape reflects the past history of fire (Sheuyange et al, 2005;Nefabas and Gambiza, 2007). Fire and grazing as natural ecosystem drivers often influence the changes in vegetation structure and composition (Roques et al, 2001).…”
Section: Why Monitor Biodiversitymentioning
confidence: 99%